Twenty lessons in environmental sociology / (Acc: P7445) - Gould, K. A. Lewis, T. L. (New York : Oxford University Press, 2021)
Twenty Lessons in Environmental Sociology introduces undergraduates to the topic in an innovative way. Instead of compiling articles from professional journals, this reader presents twenty classroom-tested "lessons" from dedicated, experienced teachers and researchers in the field. Building the collection on the model of a successful undergraduate classroom experience, the coeditors asked the contributors to choose a topic, match it with their favorite lecture, and construct a lesson to reflect the way that they teach it in the classroom. The result is an engaging and versatile volumethat presents the core ideas of environmental sociology in concise, accessible chapters.
Includes bibliographical addresses and indexes.